Redefinisi Makna Nasakh Internal Ayat Al-Qur'an - R Reflita (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2017)
Nasikh and mansukh is one of interesting studies, not only among Muslims, but also for orientalists. The alleged revision of some verses of the Qur'an is often used as an excuse for the Qur'anic authenticity by some orientalists, because of its inconsistency in establishing a rule or law. Unlike Orientalists, the internal nasakh verse of the Qur'an is believed by Muslims to have a lot of wisdom for the ease and the welfare of Muslims. The clerical debate surrounding the internal nasakh verses of the Qur'an is divided into those who believe in the existence of the nasakh and the rejecting classes. Controversy surrounding definition, kind and number of verses of nasakh need to be addressed wisely with new meaning so that can accommodate existing opinions.